PERAN HUKUM DALAM PENGATURAN DAN PERLINDUNGAN KERJA GIG ECONOMY DI INDONESIA - Emeldi, Adristi Syakirah; Rizka Humairah, Miftah; Aqilah , Nazwa (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
The Gig Economy is currently one of the many options for generation Z to work, the problem that is currently occurring is still the lack of Government attention in providing adequate guarantees of protection for Gig Economy workers so that research needs to be conducted with the aim of How the Law Plays in Regulation and Job Protection for Gig Economy Workers in Indonesia. The methodology in this research is a type of literature review research by analyzing qualitative data from various scientific articles. The results of the research show that there is still minimal attention and role of the Indonesian government for Gig Economy players. This research has a positive impact on the development of science and shows that Gig Economy workers have the right to receive regulation and protection from the government in Indonesia. Keywords: Gig Economy; Legal Role; Protection; Regulation